Pengaruh Penyajian dan Aksesibilitas Laporan Keuangan Terhadap Transparansi Pengelolaan Keuangan di Kantor Pelayanan Perbendaharaan Negara (KPPN) Surabaya II - Putri Nadiya Puspitasari; Maulidah Narastri (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research is to measure how influential the presentation of financial reports and the accessibility of financial reports are on the transparency of financial management at the State Treasury Services Office (KPPN) Surabaya II. The approach used in this research is a quantitative approach by analyzing primary data in the form of questionnaires. Primary data is data collected using the questionnaire method, which means distributing a list of questions (questionnaires) which are filled in and must be answered by employee respondents and Regional Work Units (SKPD) within the scope of KPPN Surabaya II. The population in this study was 178 Regional Work Units (SKPD). The sample used was 64 respondents. The data collection method in this research uses the Likert scale technique.